Fatores psicossociais presentes no contexto de trabalho de docentes de alunos com TDAH no IFRS - Girotto, Jéssica de Oliveira (My University, 2025)
The work of teachers with students with Attention Deficit Hyperactivity Disorder (ADHD) has been impacted by some psychosocial factors. In the literature, we can identify some of these factors and how they are present in the interactions between teachers and students with ADHD. The World Health Organization (WHO) describes psychosocial factors as aspects that define the subjective interaction between the worker and his/her role. Psychosocial factors interfere in the experience of well-being at work and also in the processes of decompensation in health, whether mental or physical. Therefore, this study has as its main objective to analyze psychosocial factors present in interactions between teachers and students with Attention Deficit Hyperactivity Disorder (ADHD). It will also contribute to the planning of interventions, assisting teachers in the influences of psychosocial risk factors that may arise during their work. The methodology used in the study was mixed (qualitative and quantitative), using the Health Safety Executive - Indicator Tool (HSE-IT) scale and a semi-structured interview script with sociodemographic data, developed by the author, as research instruments. The participants were 18 professors from the 17 campuses of the Instituto Federal do Rio Grande do Sul (IFRS). Based on the discovery of the risk and protective factors that permeate the work of these professors, a proposal for training for the institutional team was developed and it was possible to detect and act on the protective factors to strengthen them and on the risk factors to minimize them. [resumo fornecido pelo autor]
O trabalho do docente com alunos com o Transtorno do Déficit de Atenção e Hiperatividade (TDAH) vem sofrendo impactos de alguns fatores psicossociais. Na literatura, podemos identificar quais são alguns deles e como estão presentes nas interações do docente e aluno com o TDAH. A Organização Mundial da Saúde (OMS) descreve os fatores psicossociais como os aspectos que definem a interação subjetiva entre o trabalhador e sua função. Os fatores psicossociais interferem na vivência do bem-estar no trabalho e também nos processos de descompensações na saúde, seja mental ou física. Com isso, este estudo tem como objetivo principal, analisar fatores psicossociais presentes em interações entre docentes e alunos com o Transtorno do Déficit de Atenção e Hiperatividade (TDAH). Também, contribuirá para o planejamento de intervenções, auxiliando os docentes nas influências dos fatores psicossociais de risco que possam surgir no decorrer de seu trabalho. A metodologia utilizada no estudo foi mista (qualitativa e quantitativa), tendo como instrumentos de pesquisa a escala Health Safety Executive - Indicator Tool (HSE-IT) e um roteiro de entrevista semiestruturado com dados sócio demográficos, desenvolvido pela autora. Os participantes foram 18 docentes dos 17 campi do Instituto Federal do Rio Grande do Sul (IFRS). A partir da descoberta dos fatores de risco e de proteção que permeiam o trabalho destes docentes, foi desenvolvida a proposta de uma capacitação para a equipe institucional e foi possível detectar e atuar nos fatores protetivos para fortalece-los e nos fatores de risco para minimizá-los. [resumo fornecido pelo autor]
Keywords: Psicologia; Distúrbio do déficit de atenção com hiperatividade; Psicologia organizacional; Professores de ensino médio - Aspectos psicológicos; Psychology; Attention-deficit hyperactivity disorder; Organizational psychology; High school teachers - Psychological aspects